Las teorías de la excesiva onerosidad de la prestación y del riesgo, y su aplicación en los contratos de transporte marítimo internacional de mercancías: estado de la cuestión en el Perú - Pejovés Macedo, José Antonio (2023)
The COVID-19 pandemic not only had profound impacts on humanity, but also on the global economy and legal relations between international commerce actors, causing contracting parties to invoke theories of the excessive burden of the provision and the risk to balance their obligations or to terminate the contracts. This article focuses on verifying the application of the aforementioned theories of Civil Law in contracts for the maritime transport of goods, a legal relationship of Maritime Law. As is known, approximately eighty percent of international trade is moved by ship, hence the importance of analyzing impacts that the global pandemic may have had through the legal mechanisms used by the parties involved in a transport contract maritime cargo to renegotiate or terminate the contract.